1999
DOI: 10.21273/hortsci.34.3.477e
|View full text |Cite
|
Sign up to set email alerts
|

207 Tillage Methods Affect the Growth of Sweetpotato

Abstract: Growth of the sweetpotato [Ipomoea batatas (L.) Lam.] is subject to environmental variation. High soil temperatures can restrict storage root initiation and development. Moreover, fluctuating soil moisture can have a pronounced effect on yield and quality. Cover crops, used in a conservation tillage system, could modify the soil environment. The objective of this research was to investigate the effects of conservation tillage on sweetpotato growth. A rye cover crop was broadc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This study and others (Bloodworth et al 1995, Jett 1999, Stone et al 2005, Treadwell 2005) indicate that killed-cover crop mulches can be used in sweetpotato production without causing increased insect damage or reduced yields. Overall, insect injury ratings for sweetpotatoes grown under killed-cover cropping mulch in this study were not greatly different from those grown in the conventional tillage system with the same weed control.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study and others (Bloodworth et al 1995, Jett 1999, Stone et al 2005, Treadwell 2005) indicate that killed-cover crop mulches can be used in sweetpotato production without causing increased insect damage or reduced yields. Overall, insect injury ratings for sweetpotatoes grown under killed-cover cropping mulch in this study were not greatly different from those grown in the conventional tillage system with the same weed control.…”
Section: Discussionsupporting
confidence: 56%
“…A simple adaptation to a conventional planter was used in the transplantation of sweetpotato slips into heavy residue plots (Edwards et al 1998). Jett (1999) reported that sweetpotatoes grown in an undisturbed rye residue in Louisiana had a signiÞcantly greater leaf area, vine weight, root set, and yield relative to conventionally tilled sweetpotatoes, which was attributed to lower soil temperatures that increased root set. However, in one experiment, white grubs, Phyllophaga ephilida Say, were higher in the conservation tillage plots (Jett and Talbert 1997).…”
mentioning
confidence: 99%
“…In a Louisiana study of cover crop use in a conventional sweetpotato 'Beauregard' system, Jett and Talbot (1998) found that when incorporated, rye and ryegrass reduced soil erosion and increased yields of sweetpotato. In a subsequent study, sweetpotatoes growing in undisturbed rye residue had higher leaf area, vine weight, root set, and yield relative to conventional tilled sweetpotatoes (Jett, 1999). The researchers hypothesized that the cover crop residue favorably modified the soil environment by eliminating early restriction to root set often caused by high soil temperatures (Jett, 1999).…”
mentioning
confidence: 99%
“…When cover crop residues remain on the surface, weed seed germination can be inhibited because of a change in the soil microenvironment (Teasdale and Mohler 1993) as well as physical interference by the residue (Creamer et al 1996;Hutchinson and McGiffen 2000;Mohler and Teasdale, 1993). To this end, reduced tillage vegetable production has been hypothesized as an alternate system to reduce weed occurrence as well as improve soil properties (Hoyt 1999;Jett 1999).…”
mentioning
confidence: 99%